Two Theorems of Complex Analysis - Trohimchuk, Yu. Yu (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We prove two fundamental theorems of multidimensional complex analysis by the methods of this analysis without using the theory of subharmonic functions. As a single violation, we can mention the use of Green’s formula.